Assessment of Mesozoic-Kainozoic climate impact on oil-source rock potential (West Siberia); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Iskorkina A. A. Albina Albertovna (Geophysical Surveying Methods for Ore Deposit Prospecting. Geoinformation Systems in Geophysical Surveys, 2015)
Title screen